2018
DOI: 10.5334/pb.464
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Adjustment, and Psychological Distress of Help-Seeking Expatriates

Abstract: The present study aimed to explore the interrelations between support processes, adjustment, and psychological distress within a sample of help-seeking expatriates. Specifically, we examined (1) the association between expatriates’ cross-cultural adjustment (i.e., work, interaction and general adjustment) and levels of psychological distress (i.e., depression, anxiety and stress), (2) the association between expatriates’ perceptions of socioemotional and instrumental support availability and their level of cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
5
10
0
1
Order By: Relevance
“…Consistent with previous studies ( 40 , 41 ), social support from society was positively associated with mental health help-seeking. Studies have shown that social support, being prompted to seek help, and knowing someone who has sought help are associated with positive attitudes toward seeking mental health services ( 42 , 43 ) as well as perceived need and the actual behavior of mental health help-seeking ( 23 , 43 , 44 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies ( 40 , 41 ), social support from society was positively associated with mental health help-seeking. Studies have shown that social support, being prompted to seek help, and knowing someone who has sought help are associated with positive attitudes toward seeking mental health services ( 42 , 43 ) as well as perceived need and the actual behavior of mental health help-seeking ( 23 , 43 , 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…These COVID-19 work-related stressors were associated with a higher likelihood of mental health help-seeking in the adjusted analysis, which is consistent with previous studies that stress may indicate higher mental health needs and prompt Corroborating previous studies (16,21,38,39), the findings demonstrated the independent effect of psychological training on help-seeking, which implies that providing essential training is a feasible and effective approach to promote help-seeking of PHW. Consistent with previous studies (40,41), social support from society was positively associated with mental health help-seeking. Studies have shown that social support, being prompted to seek help, and knowing someone who has sought help are associated with positive attitudes toward seeking mental health services (42,43) as well as perceived need and the actual behavior of mental health help-seeking (23,43,44).…”
Section: Discussionsupporting
confidence: 91%
“…Social support has increasingly been recognized as an important source of support for people with stressful life situations (Filipič Sterle et al, 2018). In the current study, participants who did not have extended family or relatives in Australia could not rely on relatives and could not find support from their community and neighbours.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that socioemotional support strongly influences adolescent adjustment and developmental outcomes (Ni et al, 2016 ; Sterle et al, 2018 ; Wright and Wachs, 2019 ). Defined as the range of behaviors through which one person conveys love (i.e., affection or emotional acceptance) and esteem (i.e., respect or social acceptance) toward another person, socioemotional support is one of the major domains of social support satisfying the most basic emotional needs of individuals (Foa and Foa, 1974 ).…”
Section: Introductionmentioning
confidence: 99%